Gut Dysbiosis and Clostridioides difficile Infection in Neonates and Adults - Vasilescu, Iulia-Magdalena; Chifiriuc, Mariana-Carmen; Pircalabioru, Gratiela Gradisteanu; Filip, Roxana; Bolocan, Alexandra; Lazăr, Veronica; Diţu, Lia-Mara; Bleotu, Coralia (Frontiers in Microbiology, 2022)
In this review, we focus on gut microbiota profiles in infants and adults colonized (CDC) or infected (CDI) with Clostridioides difficile. After a short update on CDI epidemiology and pathology, we present the gut dysbiosis profiles associated with CDI in adults and infants, as well as the role of dysbiosis in C. difficile spores germination and multiplication. Both molecular and culturomic studies agree on a significant decrease of gut microbiota diversity and resilience in CDI, depletion of Firmicutes, Bacteroidetes and Actinobacteria phyla and a high abundance of Proteobacteria, associated with low butyrogenic and high lactic acid- bacteria levels. In symptomatic cases, microbiota deviations are associated with high levels of inflammatory markers, such as calprotectin. In infants, colonization with Bifidobacteria that triggers a local anti-inflammatory response and abundance of Ruminococcus, together with lack of receptors for clostridial toxins and immunological factors (e.g., C. difficile toxins neutralizing antibodies) might explain the lack of clinical symptoms. Gut dysbiosis amelioration through administration of ‘biotics’ or non-toxigenic C. difficile preparations and fecal microbiota transplantation proved to be very useful for the management of CDI.